(NaNTIFERROMAGNETIZM GAMMA(B-(NVELEZA (B:s (NpROBLEMA INWARA (B/s - (NsEDOW(B, (NwIKTOR lEONIDOWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1987)
(NbIBLIOGR(B.: (NS(B. 234-288s
Keywords: (NaNTIFERROMAGNETIZMs; (NfIZI^ESKOE STROENIE MATERIIs